Scope of Taxable Employment Income: a case comment on FDRE Ministry of Justice V. Tekle Garidew et al - Tsegay, Ataklti Weldeabzgi (Bahir Dar University Journal of Law, 2022)
Despite the legal frameworks as to taxable and exempted employmentincome, there are dispute relating to such issues. One such instance relates toresettlement fund or payment for loss of employment. A dispute appearedbetween the Federal Democratic Republic of Ethiopia Ministry of Justice (theapplicant), on the one hand, and Tekele Garidew et al (respondents), on theother. The case was first entertained by the Administrative Tribunal of the Federal Civil Service Agency and later on it reached to the Federal SupremeCourt on appeal. Both the Tribunal and the Appellate Court decided thatresettlement fund or payment for loss of employment is not taxable income.As a result, the case was finally taken to the Cassation Division of the FederalSupreme Court of Ethiopia which affirmed the decisions of the Tribunal andthe Appellate Court. As we will be shown below, the decision of thisCassation Division is contrary to the income tax laws and its own analysisappearing in its judgment.